Polystyrene Waste-ZnO nanocomposite film for energy harvesting via hydrophobic triboelectric nanogenerator: Transforming waste into energy - Suriani Abu Bakar (Tanjung Malim, 2024)
Polystyrene Waste-ZnO nanocomposite film for energy harvesting via hydrophobic triboelectric nanogenerator: Transforming waste into energy by Suriani Abu Bakar